A method to identify weak points of interconnection of renewable energy resources. (September 2019) - Wu, Di; Aldaoudeyeh, Al Motasem; Javadi, Milad; Ma, Feng; Tan, Jin; Jiang, John N.
Highlights: Analyze the challenges for weakness analysis based on grid strength assessment in a realistic power grid. Analyze the impact of power network structure on grid strength. Propose a method for fast weakness analysis in a realistic power grid. Verify the method in a realistic power grid. Abstract: The increasing penetration of renewable energy resources (RERs) is challenging power grid planning and operation in maintaining grid reliability. Potential power grid reliability and stability issues may arise when large-scale RERs are connected to a weak power grid. These issues may become more significant due to the mutual interactions among RERs that are interconnected electrically close through a power network. Weakness analysis based on grid strength assessment is useful for identifying the potential weak grid issues. However, when taking into account the impact of the interactions among RERs, the weakness analysis becomes computationally challenging. Different combinations of points of interconnections (POIs) of RERs may have different impacts on grid strength at each POI. Due to the combination nature, such weakness analysis may be time-consuming when identifying the weakest combination of POIs from a large number of potential candidates in realistic power grids. To address this concern, the impact of the power network structure on grid strength is analyzed in this paper. It is found that the impact mainly depends on the impedance ratios at POIs. The findings can be summarized as two criteria to develop a recursive method for fast identification of the weakest combination in this paper. The efficacy of the proposed method is demonstrated through case studies on the IEEE 39-bus system and a realistic power grid.